A COMPARATIVE STUDY OF SCREEN TIME AND ITS EFFECTS IN PRE-COVID AND COVID-ERA IN CHILDREN OF 5 TO 15 YEARS - Rajpoot, Atul; Jain, Anurag; Gupta, Preeti; Bhargava, Neeta; Vijaywargiya, Taruna; Gupta, Mahesh (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of this study was to compare the screen time (ST) in pre-COVID and COVID era in children aged 5–15 years and to analyse the ST effect in pre-COVID and COVID era in the children. Methods: The study was done at Vivekananda Polyclinic and Institute of Medical Sciences, Lucknow. Two hundred and seventy-six children aged between 5 and 15 years, attending outpatient department or inpatient department were enrolled in the study. Results: It was observed that the ST was significantly increased in post-COVID as compared to pre-COVID time and the difference was statistically significant (p<0.0001*). It was also observed that the screening time was significantly increased in post-COVID as compared to pre-COVID time and the difference was statistically significant (p<0.0001*). Conclusion: The present study found that when screening duration was analysed, the screening time during COVID-19 was significantly longer than the screening time before COVID-19 which may be associated with the various health problems reported among children during COVID-19 pandemic.